Hidden Wisdom, Esoteric Traditions and the Roots of Christian Mysticism. Second, Revised and Enlarged paperback edition. - Guy Stroumsa (Numen Book Series, 2005)
This book investigates the problem of esoteric traditions in early Christianity, their origin and their transformation in Patristic hermeneutics, in the West as well as in the East. It argues that these traditions eventually formed the basis of nascent Christian mysticism in Late Antiquity. These esoteric traditions do not reflect the influence of Greek Mystery religions, as has often been claimed, but rather seem to stem from the Jewish background of Christianity. They were adopted by various Gnostic teachings, a fact which helps explaining their eventual disappearance from Patristic literature. The eleven chapters study each a different aspect of the problem, including the questions of Gnostic and Manichaean esotericism. This book will be of interest to all students of religious history in Late Antiquity. Revised and extended paperback edition. Originally published in 1996. Please click here for details.